Promotion effects of plasma treatment on silica supports and catalyst precursors for cobalt Fischer–Tropsch catalysts. Issue 62 (15th June 2016) - Liu, Chen; Lan, Jiaping; Sun, Fenglou; Zhang, Yuhua; Li, Jinlin; Hong, Jingping
Abstract : Glow discharge plasma would modify the surface hydrophilicity of support; the plasma treated catalysts showed much higher FTS activity. Abstract : The glow discharge plasma technique was applied to decorate the silica support and to decompose the precursors of cobalt-based catalysts. The catalysts were characterized by N2 -physisorption, X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), hydrogen temperature-programmed reduction (H2 -TPR), temperature programmed desorption of H2 (H2 -TPD) and O2 -titration. The results confirmed that plasma decoration would modify both the SiO2 pore structure and surface properties. Compared with the calcined catalysts, plasma treated samples had a much higher cobalt dispersion and good cobalt reducibility, leading to an apparently improved FTS activity.